2015
DOI: 10.1080/ac.70.2.3073513
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated and unreported prolonged QTc by automated ECG analysis in patients on methadone: can we rely on computer reading?

Abstract: QTc can be underestimated or unreported by the computer analysis. Physicians not only should calculate QTc manually but also examine the actual QTc value displayed on the report before concluding that this parameter is normal, especially in patients who are at risk of QTc prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Automated QTc measurement is usually not recommended because it can underestimate QTc 21. Only recently continuous QTc measurement was validated in critically ill patients, but only in patients with QRS <120 ms 22.…”
Section: Discussionmentioning
confidence: 99%
“…Automated QTc measurement is usually not recommended because it can underestimate QTc 21. Only recently continuous QTc measurement was validated in critically ill patients, but only in patients with QRS <120 ms 22.…”
Section: Discussionmentioning
confidence: 99%
“…Automated QT measurement algorithms have proved unsatisfactory for detecting LQTS in particular [33][34][35][36][37][38][39]. Garg and Lehmann [33] found that even a widely used computerized ECG analysis system was not able to detect QT-interval prolongation in 52.5% of patients affected.…”
Section: Plos Onementioning
confidence: 99%
“…Garg and Lehmann [33] found that even a widely used computerized ECG analysis system was not able to detect QT-interval prolongation in 52.5% of patients affected. Research has also shown that drug-induced QT-prolongation can be underestimated and under-reported by computerised methods in patients on Methadone, a drug that is infamous for prolonging the QT-interval and increasing the risk of TdP [38]. A major challenge for automated QT algorithms is identifying the precise end of the T-wave (the terminal point), especially when the T-wave's morphology is abnormal [2,40,41].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Large studies have shown the sensitivity of automated ECG algorithms to be below 50% for detecting prolonged QT intervals. 4,5 Studies comparing manual 49 the available evidence supports it being in the conditional risk category 50 with computerised calculation have returned findings favouring manual assessment by trained observers; 6 however, in a large study of 902 physicians, less than 50% of cardiologists and less than 40% of other physicians were able to correctly identify a prolonged QT interval. 7 Thus, it is imperative that clinicians are able to measure the QT interval correctly, given the inaccuracies of automated measurement.…”
Section: Inaccuracies Of Qt Measurementmentioning
confidence: 99%